MEMBANGUN PENGETAHUAN PEMANFAATAN TEKNOLOGI INFORMASI DALAM LINTAS BIDANG DAN LINTAS KARIR BAGI SISWA SMA KALAM KUDUS - Carlene Lim; Viny Christanti M. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
SMA Kalam Kudus is a partner in the field of education as a non-productive economic partner. This PKM activity is carried out with the aim of increasing the knowledge of partners in seeing the use of information technology that can have an impact across fields and occupations. The implementation of this knowledge increase is carried out in the form of online seminars and evaluations. The online seminar was held because during this pandemic the educational process all changed online. Online seminar activities are carried out simultaneously between SMA Kalam Kudus II and III. After being evaluated, many students do not know that the impact of current technology changes the way they study and careers in the future. Students only know that today's technology provides convenience and is only to be enjoyed as a consumer. After going through online seminars, students can find out that there are technologies used today that affect careers and future conditions.